Endoscopic-Assisted Transoral Thyroglossal Cyst Resection - Chen, Shanwen; Wang, Dong; Qiu, Jianxin; Liu, Yehai; Zhao, Yi (Frontiers in Endocrinology, 2022)
Sistrunk procedure is the standard method for thyroglossal duct cyst resection. While this procedure is successful and safe, it results in postoperative scars on the front of neck. We propose a total transoral technique without external incision that starts with careful separation of the floor of the mouth and genioglossus muscle followed by the exact localization of the cyst using methylene blue. Simultaneously, the hyoid bone connected to the cyst and tract was removed. Finally, routine hemostasis is conducted, and the operative cavity is closed. All patients who received this operation in our department recovered successfully without experiencing severe intraoperative or postoperative complications.